Dissemination of Novel Antimicrobial Resistance Mechanisms through the Insertion Sequence Mediated Spread of Metabolic Genes - Furi, Leonardo; Haigh, Richard; Al Jabri, Zaaima J. H.; Morrissey, Ian; Ou, Hong-Yu; León-Sampedro, Ricardo; Martinez, Jose L.; Coque, Teresa M.; Oggioni, Marco R. (Frontiers in Microbiology, 2016)
The widely used biocide triclosan selectively targets FabI, the NADH-dependent trans-2-enoyl-acyl carrier protein (ACP) reductase, which is also an important target for the development of narrow spectrum antibiotics. The analysis of triclosan resistant Staphylococcus aureus isolates had previously shown that in about half of the strains, the mechanism of triclosan resistance consists on the heterologous duplication of the triclosan target gene due to the acquisition of an additional fabI allele derived from Staphylococcus haemolyticus (sh-fabI). In the current work, the genomic sequencing of ten of these strains allowed the characterisation of two novel composite transposons TnSha1 and TnSha2 involved in the spread of sh-fabI. TnSha1 harbours one copy of IS1272, whereas TnSha2 is a 11.7 kb plasmid carrying TnSha1 present either as plasmid or in an integrated form generally flanked by two IS1272 elements. The target and mechanism of integration for IS1272 and TnSha1 are novel and include targeting of DNA secondary structures, generation of blunt-end deletions of the stem-loop and absence of target duplication. Database analyses showed widespread occurrence of these two elements in chromosomes and plasmids, with TnSha1 mainly in S. aureus and with TnSha2 mainly in S. haemolyticus and S. epidermidis. The acquisition of resistance by means of an insertion sequence-based mobilisation and consequent duplication of drug-target metabolic genes, as observed here for sh-fabI, is highly reminiscent of the situation with the ileS2 gene conferring mupirocin resistance, and the dfrA and dfrG genes conferring trimethoprim resistance both of which are mobilised by IS257. These three examples, which show similar mechanisms and levels of spread of metabolic genes linked to IS elements, highlight the importance of this genetic strategy for recruitment and rapid distribution of novel resistance mechanisms in staphylococci.